Wear-resistant steel
By reducing the Ni and Mo content in the wear-resistant steel, increasing the Cr content, and optimizing the precipitation and grain structure of carbides, the problem that existing wear-resistant steels are difficult to maintain high wear resistance and low temperature toughness at the same time is solved, and the problem of existing wear-resistant steels is realized. Cost-effective improvement.
Patent Information
- Application Number
- CN202180048820.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-07-28
- Filing Date
- 2021-07-28
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2041-07-28
AI Technical Summary
When the existing wear-resistant steel reduces the use of expensive elements Ni and Mo, it is difficult to maintain high wear resistance and low temperature toughness at the same time, and it is costly.
By optimizing chemical composition and heat treatment processes, the Ni and Mo content are reduced, the Cr content is increased, and surface hardness and low-temperature toughness are ensured by controlling the precipitation of carbides and grain structure.
It is achieved without increasing the alloy cost, and the production cost of wear-resistant steel is reduced.
Smart Images

Figure BDA0004044005600000171 
Figure BDA0004044005600000201 
Figure BDA0004044005600000221
Abstract
Description
Technical Field
[0001] The present disclosure relates to wear resistant steels. Background Art
[0002] Wear-resistant steels require hardness near the surface layer, so they contain elements that improve hardenability. Cr, Ni, and Mo are elements that improve hardenability. Wear-resistant steels containing Cr, Ni, Mo, etc. have been proposed in the past (for example, refer to Patent Documents 1 to 4).
[0003] In addition, a steel plate having high strength and improved toughness has been proposed (for example, refer to Patent Document 5).
[0004] Patent Document 1: Japanese Patent Application Laid-Open No. 10-204575
[0005] Patent Document 2: Japanese Patent Application Laid-Open No. 10-102185
[0006] Patent Document 3: Japanese Patent Application Laid-Open No. 59-129724
[0007] Patent Document 4: Japanese Patent Application Laid-Open No. 59-70721
[0008] Patent Document 5: International Publication No. 2019 / 050010 Summary of the invention
[0009] Problems to be solved by the invention
[0010] The wear-resistant steels of Patent Documents 1 and 2 contain 1.0 mass % or more of Mo. The wear-resistant steels of Patent Documents 3 and 4 contain 2.0 mass % or more of Ni. Ni and Mo are expensive elements, and reduction is desired from the viewpoint of alloy cost.
[0011] Furthermore, although the high-strength steel sheet of Patent Document 5 achieves improved toughness, wear resistance is not considered.
[0012] In view of such actual conditions, an object of the present disclosure is to provide a wear-resistant steel having excellent wear resistance and low-temperature toughness while suppressing the use of expensive elements such as Ni and Mo.
[0013] Means for solving problems
[0014] The gist of the present disclosure is as follows.
[0015] (1) A wear-resistant steel, the chemical composition of which is composed of the following elements in mass %:
[0016] C: 0.08% to 0.20%,
[0017] Si: 0.01% to 0.50%,
[0018] Mn: 0.10% to 2.00%,
[0019] P: 0.015% or less,
[0020] S: 0.0300% or less,
[0021] Cr: 2.10%~8.00%,
[0022] N: 0.008% or less,
[0023] Cu: 0% to 0.50%,
[0024] Ni: 0% to 0.50%,
[0025] Mo: 0% to 0.50%,
[0026] V: 0%~0.500%,
[0027] W: 0%~0.50%,
[0028] B: 0%~0.0050%,
[0029] Al: 0% to 0.300%,
[0030] Ti: 0% to 0.100%,
[0031] Nb: 0% to 0.100%,
[0032] Ca: 0% to 0.0100%,
[0033] Mg: 0% to 0.0100%,
[0034] REM: 0% to 0.0100%, and
[0035] The rest: Fe and impurities,
[0036] In a cross section in the thickness direction, when the thickness is set to t, when t is less than 16 mm, it is at a position 1 / 2t from the surface, and when t is 16 mm or more, it is at a position 1 / 4t from the surface, the carbides contained in the metal structure are 0% to 0.5% in terms of area %, the average equivalent circle diameter of the above carbides is 500nm or less, in a region of 400μm×400μm, the average grain size of the first 10 grains in order of the largest grain size among the grains surrounded by grain boundaries with a large inclination angle of 15° or more is 40μm or less, and the Charpy absorption energy at -40°C is 27J or more,
[0037] When the C content in mass % is set to [C], the surface hardness at a position 0.7 mm from the surface in the thickness direction is 360 HV10 or more and 634×[C] 1 / 2 +140HV10 and above.
[0038] (2) The wear-resistant steel according to claim 1, wherein the central hardness of the central portion in the thickness direction is 360 HV10 or more and 634×[C] 1 / 2 +140HV10 and above.
[0039] (3) The wear-resistant steel according to (1) or (2), which contains, in terms of mass%, at least one selected from the following elements:
[0040] Cu: 0.01% to 0.50%,
[0041] Ni: 0.01% to 0.50%,
[0042] Mo: 0.01% to 0.50%,
[0043] V: 0.003%~0.500%,
[0044] W: 0.01%~0.50%,
[0045] B: 0.0003% to 0.0050%,
[0046] Al: 0.005% to 0.300%,
[0047] Ti: 0.003% to 0.100%,
[0048] Nb: 0.003% to 0.100%,
[0049] Ca: 0.0003% to 0.0100%,
[0050] Mg: 0% to 0.0100%, and
[0051] REM: 0.0003% ~ 0.0100%.
[0052] (4) The wear-resistant steel according to any one of (1) to (3), which is a steel plate.
[0053] (5) The wear-resistant steel according to (4), wherein the thickness of the steel plate is 8 mm to 50 mm.
[0054] Effects of the Invention
[0055] According to the present disclosure, it is possible to provide wear-resistant steel that suppresses the use of expensive elements such as Ni and Mo and has excellent wear resistance and low-temperature toughness. By reducing the alloy cost of wear-resistant steel, it is possible to provide cheap wear-resistant steel. Therefore, the present disclosure has a very significant contribution to the industry. DETAILED DESCRIPTION
[0056] Hereinafter, as the wear-resistant steel according to one embodiment of the present disclosure (hereinafter referred to as “the present embodiment”), a steel plate will be mainly described.
[0057] In the numerical ranges recorded in stages in this specification, the upper limit of a numerical range in a certain stage may be replaced by the upper limit of a numerical range recorded in other stages, and the lower limit of a numerical range in a certain stage may be replaced by the lower limit of a numerical range recorded in other stages. The upper limit or lower limit may also be replaced by the value shown in the embodiment.
[0058] The term "process" includes not only independent processes but also processes that cannot be clearly distinguished from other processes as long as the intended purpose of the process can be achieved.
[0059] First, the research results and new findings obtained by the inventors of the present invention leading to the completion of the present disclosure will be described in detail.
[0060] Cr is an element cheaper than Ni and Mo. By suppressing the content of Ni and Mo and increasing the Cr content, the cost of wear-resistant steel can be reduced. As a result of research by the inventors of the present invention, it is found that the Cr content required for alloy-saving wear-resistant steel is 2.10% or more when Ni and Mo are not intentionally contained or when the content of Ni and Mo is suppressed to less than 0.50%, respectively. It is further found that by increasing the Cr content in this way, the corrosion resistance is also improved, which helps to prolong the life of wear-resistant steel used in wet environments.
[0061] On the other hand, in order to ensure the surface hardness of the wear-resistant steel, it is preferable to increase the C content, but this will cause a problem of reduced toughness.
[0062] The inventors of the present invention have successfully achieved both surface hardness and toughness of wear-resistant steel by suppressing the precipitation and coarsening of carbides. As a result of their research, the inventors of the present invention have found that by limiting the C content and the stop temperature of quenching, the precipitation and coarsening of carbides can be suppressed to ensure toughness. Specifically, it was found that if the C content is set to less than 0.20% and the stop temperature of quenching is set to less than 200°C, the precipitation and coarsening of carbides can be effectively suppressed. It was found that when the area ratio of carbides is less than 0.5% and the average equivalent circle diameter is less than 500nm, the surface hardness is greater than 360HV10 in Vickers hardness and is 634×[C] when the C content is set to [C]. 1 / 2 In the case of +140HV10 or more, the total area ratio of one or both of martensite and lower bainite is 95% or more.
[0063] <Chemical Composition>
[0064] Next, alloy elements constituting the chemical composition of the steel sheet according to the present embodiment will be described. In the following description of alloy elements, "%" of content means "mass %".
[0065] [C: 0.08% to 0.20%]
[0066] C (carbon) is an element that improves the hardenability of steel and increases hardness. From the viewpoint of ensuring hardness, the C content is 0.08% or more. The C content is preferably 0.10% or more. On the other hand, C is an element that generates carbides. From the viewpoint of ensuring toughness, the C content is 0.20% or less. The C content is preferably 0.18% or less, and more preferably 0.15% or less.
[0067] [Si: 0.01% to 0.50%]
[0068] Si (silicon) is a deoxidizing element. From the viewpoint of obtaining a deoxidizing effect, the Si content is 0.01% or more. The Si content is preferably 0.05% or more, and more preferably 0.10% or more. On the other hand, from the viewpoint of ensuring toughness, the Si content is 0.50% or less. The Si content is preferably 0.40% or less, and more preferably 0.30% or less.
[0069] [Mn: 0.10% to 2.00%]
[0070] Mn (manganese) is an element that improves the hardenability of steel. From the viewpoint of ensuring hardness, the Mn content is 0.10% or more. The Mn content is preferably 0.50% or more, more preferably 0.80% or more, and further preferably 1.00% or more. On the other hand, Mn is an element that embrittles the crystal grain boundaries of steel. From the viewpoint of ensuring toughness, the Mn content is 2.00% or less. The Mn content is preferably 1.80% or less, and more preferably 1.60% or less.
[0071] [P: 0.015% or less]
[0072] P (phosphorus) is an element mixed into steel during the raw materials and manufacturing process. From the viewpoint of ensuring toughness, the P content is 0.015% or less. The P content is preferably 0.012% or less, and more preferably 0.010% or less. It is preferred to reduce the P content, and there is no lower limit, but from the viewpoint of manufacturing cost, it can exceed 0%. The P content can also be 0.001% or more.
[0073] [S: 0.0300% or less]
[0074] S (sulfur) is an element mixed into steel during the raw materials and manufacturing process. From the viewpoint of ensuring toughness, the S content is 0.0300% or less. The S content is preferably 0.0050% or less, and more preferably 0.0030% or less. It is preferred to reduce the S content, and there is no lower limit, but from the viewpoint of manufacturing cost, it may exceed 0%. The S content may also be 0.0001% or more.
[0075] [Cr: 2.10%~8.00%]
[0076] Cr (chromium) is an element that improves the hardenability of steel. Cr is an important element from the viewpoint of suppressing the content of expensive elements such as Ni and Mo to ensure the hardness and toughness of wear-resistant steel. From the viewpoint of ensuring hardenability, the Cr content is 2.10% or more. The Cr content is preferably 2.20% or more, more preferably 2.40% or more. On the other hand, from the viewpoint of cost, the Cr content is 8.00% or less, and may also be 7.50% or less. The Cr content is preferably 5.00% or less, more preferably 3.00% or less.
[0077] [N: 0.0080% or less]
[0078] N (nitrogen) is an element mixed into steel during the raw materials and manufacturing process. From the viewpoint of ensuring toughness, the N content is less than 0.0080%. The N content is preferably less than 0.0070%, and more preferably less than 0.0060%. It is preferred to reduce the N content, and there is no lower limit, but from the viewpoint of manufacturing cost, it can exceed 0%. When Al or Ti is contained, it will combine with N to form fine nitrides such as AlN and TiN. From the viewpoint of the refinement of the metal structure brought about by nitrides, the N content is preferably more than 0.0010%, and more preferably more than 0.0020%.
[0079] The wear-resistant steel of the present embodiment may contain one or two or more of Cu, Ni, Mo, V, W and B within the following ranges as required in order to improve hardenability without excessively increasing the manufacturing cost.
[0080] [Cu: 0% to 0.50%]
[0081] Cu (copper) is an element that improves the hardenability of steel. The lower limit of Cu content is not limited, and may be 0%. In order to reliably obtain the effect, Cu content is preferably more than 0.01%, more preferably more than 0.03%. On the other hand, from the viewpoint of cost, Cu content is less than 0.50%. Cu content is preferably less than 0.30%, less than 0.10%, and may be less than 0.05%.
[0082] [Ni: 0% to 0.50%]
[0083] Ni (nickel) is an element that improves the hardenability of steel. The lower limit of the Ni content is not limited and may be 0%. In order to obtain the effect, the Ni content is preferably 0.01% or more, more preferably 0.03% or more. On the other hand, from the viewpoint of cost, the Ni content is 0.50% or less. The Ni content is preferably 0.30% or less, more preferably 0.10% or less, and further preferably 0.05% or less.
[0084] [Mo: 0% to 0.50%]
[0085] Mo (molybdenum) is an element that improves the hardenability of steel. The lower limit of the Mo content is not limited, and it can also be 0%. In order to obtain the effect, the Mo content is preferably 0.01% or more, and more preferably 0.03% or more. On the other hand, from the perspective of cost, the Mo content is 0.50% or less. It is preferably 0.30% or less, more preferably 0.10% or less, and further preferably 0.05% or less.
[0086] [V: 0%~0.500%]
[0087] V (vanadium) is an element that forms precipitates such as carbides or nitrides, and has the effect of improving hardenability. The lower limit of the V content is not limited, and it can also be 0%. In order to obtain the effect, the V content is preferably 0.003% or more, and more preferably 0.005% or more. On the other hand, from the perspective of cost, the V content is 0.500% or less. It is preferably 0.300% or less, more preferably 0.100% or less, and further preferably 0.050% or less.
[0088] [W: 0% to 0.50%]
[0089] W (tungsten) is an element that improves the hardenability of steel. The lower limit of the W content is not limited, and it can also be 0%. In order to reliably obtain the effect, the W content is preferably 0.01% or more, and more preferably 0.03% or more. On the other hand, from the perspective of cost, the W content is 0.50% or less. The W content is preferably 0.30% or less, more preferably 0.10% or less, and further preferably 0.05% or less.
[0090] [B: 0%~0.0050%]
[0091] B (boron) is an element that significantly improves the hardenability of steel even in trace amounts. The lower limit of the B content is not limited and may be 0%. In order to obtain the effect, the B content is preferably 0.0003% or more, more preferably 0.0005% or more, and further preferably 0.0008% or more. On the other hand, even if B is contained excessively, the effect is saturated, so the B content is 0.0050% or less. The B content is preferably 0.0045% or less, and more preferably 0.0040% or less.
[0092] The wear-resistant steel of the present embodiment may contain one or two or more of Al, Ti, Nb, Ca, Mg and REM which form compounds such as carbides, nitrides, oxides and sulfides, as required.
[0093] [Al: 0% to 0.300%]
[0094] Al (aluminum) is a deoxidizing element and also an element that forms nitrides. The lower limit of the Al content is not limited and can also be 0%. In order to obtain a deoxidizing effect, the Al content is preferably 0.005% or more. From the viewpoint of the refinement of the metal structure brought about by AlN, the Al content is more preferably 0.010% or more. On the other hand, from the viewpoint of suppressing the formation of coarse inclusions, the Al content is 0.300% or less. The Al content is preferably 0.100% or less, and more preferably 0.070% or less.
[0095] [Ti: 0% to 0.100%]
[0096] Ti (titanium) is a deoxidizing element and also an element that forms nitrides. In addition, when Ti contains B in steel, it is used to suppress the formation of BN and improve hardenability. The lower limit of the Ti content is not limited and can also be 0%. In order to obtain a deoxidizing effect, the Ti content is preferably 0.003% or more. From the viewpoint of the refinement of the metal structure brought about by TiN, the Ti content is more preferably 0.005% or more, and further preferably 0.010% or more. On the other hand, from the viewpoint of suppressing the formation of coarse inclusions, the Ti content is less than 0.100%. The Ti content is more preferably less than 0.050%, and further preferably less than 0.030%.
[0097] [Nb: 0% to 0.100%]
[0098] Nb (niobium) is an element that forms precipitates such as carbides or nitrides. The lower limit of the Nb content is not limited and may be 0%. From the viewpoint of the refinement of the metal structure brought about by the precipitates, the Nb content is preferably 0.003% or more, more preferably 0.005% or more, and further preferably 0.010% or more. On the other hand, even if Nb is contained excessively, the effect is saturated, so the Nb content is 0.100% or less. The Nb content is preferably 0.050% or less, and further preferably 0.030% or less.
[0099] [Ca: 0% to 0.0100%]
[0100] Ca (calcium) is an element that forms oxides or sulfides and controls the morphology of inclusions. The lower limit of the Ca content is not limited and can also be 0%. In order to obtain the effect, the Ca content is preferably 0.0003% or more. The Ca content is more preferably 0.0005% or more, and further preferably 0.0010% or more. On the other hand, from the viewpoint of suppressing the formation of coarse inclusions, the Ca content is 0.0100% or less. The Ca content is preferably 0.0080% or less, and more preferably 0.0060% or less.
[0101] [Mg: 0% to 0.0100%]
[0102] Mg (magnesium) is an element that forms oxides or sulfides and controls the morphology of inclusions. The lower limit of the Mg content is not limited and may be 0%. In order to obtain the effect, the Mg content is preferably 0.0003% or more, more preferably 0.0005% or more, and further preferably 0.0010% or more. On the other hand, from the perspective of cost, the Mg content is 0.0100% or less. The Mg content is preferably 0.0080% or less, and more preferably 0.0060% or less.
[0103] [REM: 0%~0.0100%]
[0104] REM (rare earth elements) is a general term for 17 elements in total, including two elements, Sc and Y, and 15 elements, lanthanoid elements, such as La, Ce, and Nd. The REM content is the total content of the above 17 elements.
[0105] REM is an element that forms oxides or sulfides and controls the morphology of inclusions. The lower limit of the REM content is not limited and may be 0%. In order to obtain the effect, the REM content is preferably 0.0003% or more, more preferably 0.0005% or more, and further preferably 0.0010% or more. On the other hand, from the perspective of cost, the REM content is 0.0100% or less. The REM content is preferably 0.0080% or less, and more preferably 0.0060% or less.
[0106] The remainder of the chemical composition of the steel of the present embodiment is Fe and impurities. Here, impurities refer to components that are not intentionally contained when the wear-resistant steel of the present embodiment is manufactured industrially, but are mixed in by various factors such as raw materials such as ore and scrap or in the manufacturing process. The inclusion of impurities is allowed within a range that does not adversely affect the characteristics of the wear-resistant steel of the present embodiment.
[0107] As an impurity, for example, O (oxygen) is an element mixed into steel during the raw materials and the manufacturing process. Since O is an impurity, the O content is preferably 0.0060% or less. The O content is more preferably 0.0050% or less, and further preferably 0.0040% or less. It is preferred to reduce the O content, and there is no lower limit, but from the viewpoint of manufacturing cost, it may exceed 0%. The O content may also be 0.0020% or more.
[0108] <Metallic Structure>
[0109] Next, the metal structure of the wear-resistant steel of the present embodiment will be described. Hereinafter, "%" of the metal structure means "area %".
[0110] The carbides contained in the metal structure of the wear-resistant steel of the present embodiment are 0% to 0.5% in terms of area %. The average equivalent circle diameter of the carbides is 500nm or less. In the area of 400μm×400μm, the average grain size of the first 10 grains in the order of the largest grain size in the area surrounded by large-angle grain boundaries (sometimes also referred to as "high-angle grain boundaries") of 15° or more (regarded as grains) is 40μm or less. It should be noted that, as carbides, cementite (Fe3C), Cr carbide, and Fe2C can be listed, but the carbides in the present disclosure are mainly cementite.
[0111] The metal structure of the wear-resistant steel of the present embodiment only needs the area ratio of carbides and the average equivalent circle diameter and the average grain size of the crystals to be within the above ranges. However, if upper bainite or pearlite is generated, the area ratio of carbides increases and is prone to coarsening. If ferrite is generated, the hardness is likely to be insufficient, which may reduce toughness. Retained austenite becomes hard martensite (process-induced martensite) through deformation, which may reduce toughness. Therefore, the metal structure of the wear-resistant steel of the present embodiment preferably includes one or both of martensite and lower bainite. The total area ratio of martensite and lower bainite is preferably 95% or more. The remainder other than martensite and lower bainite includes one or more of ferrite, pearlite, retained austenite and upper bainite.
[0112] It should be noted that upper bainite is a structure with a grain size of 40 μm or more that does not contain carbides in the grains and precipitates cementite or retained austenite at the grain boundaries. Martensite and lower bainite are lath-shaped hard phases, which are generally distinguished by the presence or absence of carbides. In the case where the metal structure of the wear-resistant steel of the present embodiment includes martensite and lower bainite, the metal structure containing carbides is regarded as lower bainite. In the present embodiment, it is not necessary to distinguish between martensite and lower bainite. In the case where ferrite, pearlite, retained austenite and upper bainite are not observed through an optical microscope, it is judged that the metal structure includes one or both of martensite and lower bainite.
[0113] The wear-resistant steel of the present embodiment may include metal structures other than martensite and lower bainite as long as the area ratio and average circle equivalent diameter of carbides and the average grain size of crystals are within the above-mentioned ranges.
[0114] When the thickness of the wear-resistant steel is less than 16 mm, the metal structure is observed at a position that is 1 / 2 of the thickness in the thickness direction from the surface (hereinafter also referred to as the "1 / 2t portion". In addition, "1 / 2t" and "t / 2" have the same meaning). When the thickness of the wear-resistant steel is more than 16 mm, the metal structure is observed at a position that is 1 / 4 of the thickness in the thickness direction from the surface (hereinafter also referred to as the "1 / 4t portion". In addition, "1 / 4t" and "t / 4" have the same meaning). The observation surface of the sample used in the observation of the metal structure is a cross section obtained by cutting along the L (length) direction (rolling direction) of the sample in the thickness direction (hereinafter sometimes referred to as the "L (length) direction cross section of the sample"), and wet grinding and etching with nitric alcohol are performed. The observation of the metal structure is carried out at a magnification of 400 times, and the presence or absence of ferrite, pearlite, retained austenite and upper bainite is determined by observation of 5 fields of view. Furthermore, retained austenite was observed by LePera corrosion using a 1% to 10% pyrosulfite solution.
[0115] [Area ratio of carbides: 0% to 0.5%]
[0116] In the case where the metal structure of the wear-resistant steel of the present embodiment includes martensite, the area ratio of carbides is 0%. In the case where the metal structure of the wear-resistant steel of the present embodiment includes martensite and lower bainite, the metal structure including carbides is regarded as lower bainite. From the viewpoint of ensuring toughness, the area ratio of carbides is 0.5% or less. The area ratio of carbides is preferably 0.4% or less, and more preferably 0.3% or less. If the quenching stop temperature is lowered, the formation of upper bainite and pearlite can be suppressed, and the area ratio of carbides is reduced.
[0117] The area ratio of carbides is measured by a scanning electron microscope (Scanning Electron Microscope, hereinafter referred to as "SEM"). When the thickness of the wear-resistant steel is less than 16 mm, the area ratio of carbides is measured at the 1 / 2t portion. When the thickness of the wear-resistant steel is more than 16 mm, the area ratio of carbides is measured at the 1 / 4t portion. The observation surface of the sample used in the measurement of the area ratio of carbides is the L (length) direction cross section of the sample, and electrolytic etching is performed. The area ratio of carbides is measured by image analysis (binarization by image processing) of a photograph taken at 30,000 times. Here, electrolytic etching is performed at 20 to 40 V for 10 seconds to 30 seconds using a solution obtained by mixing 62 cc of perchloric acid, 700 cc of ethanol, 137 cc of distilled water, and 100 cc of butyl cellosolve. The binarization performed by image processing sets the threshold value in such a way that the carbides precipitated in the martensite lath blocks can be separated by visual inspection.
[0118] [Average equivalent circle diameter of carbides: 500nm or less]
[0119] From the viewpoint of ensuring toughness, the average equivalent circle diameter of carbides is less than 500nm. The average equivalent circle diameter of carbides is preferably less than 300nm. The average equivalent circle diameter of carbides can also be more than 50nm, or more than 100nm. The average equivalent circle diameter of carbides is calculated by the area (total) of carbides and the number of carbides obtained by image analysis of the SEM photograph used in the determination of the area ratio. That is, the average equivalent circle diameter is calculated by the average area of carbides obtained by dividing the total area of carbides by the number of carbides. In the case where the area ratio of carbides is 0%, the average equivalent circle diameter is 0nm. If the quenching stop temperature is reduced, the formation of upper bainite and pearlite can be suppressed, and the average equivalent circle diameter of carbides becomes smaller. The average equivalent circle diameter and area ratio of carbides contained in upper bainite and pearlite are large. When the area ratio of carbides is 0.5% or less and the average equivalent circle diameter is 500 nm or less, it can be judged that the total area ratio of upper bainite and pearlite is less than 5%.
[0120] [Average of the top 10 grain sizes surrounded by grain boundaries with a high inclination angle of 15° or more: 40 μm or less]
[0121] The average of the top 10 grain sizes (the first 10 crystal grain sizes in order of largest grain size) surrounded by large-angle grain boundaries of 15° or more in an area of 400μm×400μm is less than 40μm. Hereinafter, the grain size surrounded by large-angle grain boundaries with a crystal orientation difference of 15° or more is referred to as a large-angle grain size. If the large-angle grain size becomes larger, it becomes easier to fracture, and if the large-angle grain size becomes smaller, the toughness improves. The large-angle grain size is evaluated by the average value of the top 10 grains (the first 10 from the largest) in the grains in the area of 400μm×400μm. The average of the top 10 large-angle grain sizes is more preferably less than 30μm.
[0122] In the present embodiment, the high-angle grain size is measured by electron backscatter diffraction pattern (hereinafter also referred to as "EBSD"). The measurement using EBSD is performed at a spacing of 0.4 μm in a field of view of 400 μm×400 μm. The grain size distribution is represented by commercially available analysis software (OIM-Analysis manufactured by TSL), and the average of the upper 10 grain sizes in the grains surrounded by high-angle grain boundaries of 15° or more is calculated. The measurement using EBSD is performed at the 1 / 2t portion when the thickness of the wear-resistant steel is less than 16 mm. When the thickness is more than 16 mm, the measurement is performed using EBSD at the 1 / 4t portion. The observation surface of the sample used in the measurement using EBSD is 10 mm square, cut out from a position (1 / 4 width) where the distance from the end in the width direction of the steel plate is 1 / 4 of the plate width. The observation surface is a cross section in the L (length) direction of the sample, and electrolytic grinding is performed.
[0123] Next, the surface hardness of the wear-resistant steel of the present embodiment, the hardness at the 1 / 2t portion, and the low-temperature toughness of the wear-resistant steel will be described.
[0124] [Surface hardness: 360HV10 or above and 634×[C] 1 / 2 +140HV10 or above]
[0125] The surface hardness of the wear-resistant steel of the present embodiment is 360 HV10 or more and 634×[C] in Vickers hardness in order to ensure wear resistance. 1 / 2 +140HV10 or more. [C] is the C content in the wear-resistant steel. The surface hardness of the wear-resistant steel is preferably 360HV10 or more and 634×[C] 1 / 2+160HV10 or more, more preferably 360HV10 or more and 634×[C]1 / 2+180HV10 or more. The higher the surface hardness, the better, and there is no upper limit. From the perspective of ensuring toughness, the surface hardness of the wear-resistant steel can also be 634×[C] 1 / 2 +230HV10 or less.
[0126] Considering the influence of decarburization, the surface hardness of the wear-resistant steel is measured at a position 0.7 mm from the surface of the wear-resistant steel in the thickness direction. The Vickers hardness test is carried out in accordance with JIS Z 2244: 2009, with a load of 10 kgf. The Vickers hardness is the average value of 3 points measured in the L (length) direction section of the sample. When the surface hardness is 360 HV10 or more and 634 × [C] 1 / 2 In the case of +140 HV10 or more, it can be judged that the total area ratio of ferrite and retained austenite is less than 5%.
[0127] It should be noted that from the perspective of ensuring absolute wear resistance that is not dependent on the C content, rather than ensuring relative wear resistance that takes into account the C content, the surface hardness of the wear-resistant steel of this embodiment may be 380 HV10 or more, 400 HV10 or more, or 450 HV10 or more.
[0128] [Central hardness at the center of the thickness direction: 360 HV10 or more and 634 × [C] 1 / 2 +140HV10 or above]
[0129] The central part in the thickness direction of the wear-resistant steel has the same meaning as the 1 / 2t part. Hereinafter, the central part hardness in the central part in the thickness direction of the wear-resistant steel is also referred to as the 1 / 2t part hardness. From the viewpoint of preventing deterioration of wear resistance due to use, the 1 / 2t part hardness is preferably 360 HV10 or more and 634×[C] in Vickers hardness. 1 / 2 +140HV10 or more, more preferably 360HV10 or more and 634×[C] 1 / 2 +160HV10 or more. The 1 / 2t portion hardness is more preferably 360HV10 or more and 634×[C] 1 / 2 +180HV10 or above, the higher the better, and there is no upper limit. From the perspective of ensuring toughness, the hardness of the 1 / 2t portion may be 634×[C] 1 / 2 +230HV10 or less. The Vickers hardness test is carried out in accordance with JIS Z 2244:2009, with a load of 10kgf. The Vickers hardness is the average value of three points measured in the L (length) direction section of the sample. The 1 / 2t part hardness is ensured by increasing the content of the alloy that improves the hardenability and increasing the cooling rate of quenching.
[0130] It should be noted that from the perspective of ensuring absolute wear resistance that is not dependent on the C content, rather than ensuring relative wear resistance that takes into account the C content, the central hardness of the central part of the wear-resistant steel of this embodiment may be greater than 380 HV10, greater than 400 HV10, or greater than 450 HV10.
[0131] [Average value of Charpy absorption energy at -40°C: 27J or more]
[0132] Wear-resistant steel may be used in cold regions or plateaus. In order to suppress fractures caused by impact during processing and use, wear-resistant steel needs to ensure toughness at -40°C. From this point of view, the average value of the Charpy absorbed energy of the wear-resistant steel of this embodiment at -40°C is 27J or more. The average value of the Charpy absorbed energy at -40°C is preferably 50J or more. The higher the average value of the Charpy absorbed energy at -40°C, the more preferred it is, and there is no upper limit, but it can also be 100J or less.
[0133] The Charpy test is carried out in accordance with JIS Z 2242:2018 using a full-size test piece with a V-notch. When the thickness of the wear-resistant steel is 12 mm or less, a small-size test piece of 5 mm is used. Regarding the sampling position of the Charpy test piece, the wear-resistant steel with a plate thickness of 16 mm or more is the 1 / 4t section, and the wear-resistant steel with a plate thickness of less than 16 mm is the 1 / 2t section. The length direction of the Charpy test piece is the rolling direction. Taking into account the unevenness of the measured values, the average value of the Charpy absorbed energy is the arithmetic mean of the measured values of the three test pieces.
[0134] The shape of the wear-resistant steel of the present embodiment is not particularly limited, and may be a steel plate, a steel strip, a steel section, a steel pipe, a steel bar, a steel wire, etc. The thickness of the steel plate, steel strip, steel section, steel pipe, etc. is not particularly limited, and may be, for example, 8 mm to 50 mm. The thickness of the steel may be 10 mm or more, or 16 mm or more. The thickness of the steel may be 45 mm or less, or 40 mm or less.
[0135] When the wear-resistant steel of the present embodiment is a steel bar, the diameter may be regarded as the thickness and the Vickers hardness measurement or the Charpy test may be performed.
[0136] In addition, the wear-resistant steel of the present embodiment is also excellent in corrosion resistance. When evaluating the corrosion resistance of the wear-resistant steel of the present embodiment, the test method of JASO M609 and JASO M610 is used as the basis, and an artificial seawater solution in which the solution is diluted 1 / 100 is used. 2 hours of salt water spray, 4 hours of drying, and 2 hours of wetting are regarded as one cycle. After the corrosion treatment based on 504 cycles, the rust is removed by pickling treatment, and the corrosion rate is compared by the weight change before and after corrosion. In such a corrosion resistance test, the wear-resistant steel of the present embodiment can suppress the corrosion rate to less than 80% compared with the ordinary steel SM490.
[0137] <Manufacturing method>
[0138] Next, a method for producing the wear-resistant steel according to the present embodiment will be described.
[0139] The wear-resistant steel of this embodiment is manufactured by using a steel billet obtained by melting steel, adjusting the composition, and then casting as a steel raw material. The steel raw material is hot rolled and directly quenched, or air cooled. After air cooling, it is reheated and quenched. After quenching after hot rolling, it can also be reheated and quenched.
[0140] The method for producing the steel material used for producing the wear-resistant steel of the present embodiment is not limited, and the steel material can be produced by a known method.
[0141] For example, a steel slab is melted in a conventional refining process such as a converter or an electric furnace, and then produced by a known method such as a continuous casting method or an ingot-casting method.
[0142] The steel billet is preferably cooled after casting and then heated to A. c3 Hot rolling is performed at a temperature above the phase transformation point. If the continuously cast steel billet is loaded into a heating furnace by hot charging without cooling to below 400°C, the coarse austenite generated during casting may also remain in the heated steel billet. In order to promote the refinement of the structure of wear-resistant steel, the continuously cast steel billet is preferably temporarily cooled to below 400°C.
[0143] The temperature of the surface of the rolled material during hot rolling is A r3 It is carried out in the temperature range above the phase transition point. r3 The transformation point is the temperature at which the phase transformation from austenite to ferrite begins during cooling. The heating temperature of the steel material before hot rolling is preferably 900°C or higher, more preferably 1000°C or higher, and further preferably 1100°C or higher. In order to suppress the coarsening of the grains, the heating temperature is preferably 1330°C or lower. The heating temperature is more preferably 1200°C or lower, and further preferably 1150°C or lower.
[0144] In the hot rolling of wear-resistant steel, it is preferred to promote recrystallization to reduce the grain size of austenite from the viewpoint of ensuring low-temperature toughness. In order to promote recrystallization, the reduction rate in the temperature range of 1000°C or more is preferably 50% or more. The reduction rate in the temperature range of 1000°C or more (abbreviated as reduction rate) is calculated from the thickness of the steel raw material before hot rolling and the thickness of the rolled material at 1000°C by the following formula.
[0145] Reduction ratio (%) = 100 × {(thickness of steel material) - (thickness of rolled material at 1000°C)} / thickness of steel material
[0146] From the viewpoint of preventing the formation of ferrite, the end temperature of hot rolling is A r3 When the rolled material is quenched directly after hot rolling, the hot rolling end temperature is 770°C or higher. On the other hand, from the viewpoint of refinement of the metal structure, the hot rolling end temperature is preferably 900°C or lower, more preferably 850°C or lower.
[0147] The thickness of the rolled material after hot rolling is the thickness of the wear-resistant steel, for example, 8 mm to 50 mm. When the reduction rate in hot rolling is small and the thickness is too large, the γ grain size may be coarsened, resulting in insufficient toughness. In addition, an area with insufficient hardenability is generated, and upper bainite is generated, resulting in insufficient toughness. If the thickness is 50 mm or less, the lack of toughness can be suppressed. On the other hand, if the thickness is 8 mm or more, sufficient strength can be ensured as a wear-resistant steel.
[0148] The rolled material after hot rolling is directly quenched or air-cooled. The rolled material after air cooling is reheated and quenched. The process of directly quenching the rolled material after hot rolling is called direct quenching. The process of air cooling, reheating and quenching the rolled material after hot rolling is called reheating quenching. The rolled material that has been quenched after hot rolling can also be reheated and quenched. From the viewpoint of preventing the formation of ferrite, the reheating temperature is A c3 The reheating temperature is preferably 850°C or higher, more preferably 900°C or higher. From the viewpoint of miniaturization of the metal structure, the reheating temperature is preferably 1150°C or lower. The reheating temperature is more preferably 1050°C or lower, and further preferably 1000°C or lower.
[0149] In the following description of the starting temperature, cooling rate, and stop temperature of quenching, there is no difference caused by the difference in the process of direct quenching and reheating quenching. From the viewpoint of preventing the formation of ferrite, the starting temperature of quenching is above 770°C. From the viewpoint of preventing the formation of ferrite and inhibiting the precipitation and growth of carbides, the cooling rate of quenching is above 3°C / second based on the surface temperature of the rolled material. The faster the cooling rate, the better, but there is a limit depending on the capacity of the cooling equipment, the thickness of the rolled material, etc., and it can be below 50°C / second. In addition, the cooling rate is a value calculated by the following formula.
[0150] Cooling rate = (surface temperature at the start of cooling - surface temperature at the end of cooling) / cooling time
[0151] Here, "surface temperature when cooling is stopped" refers to the surface temperature of the rolled material at the time when water cooling is stopped (not the reheating temperature).
[0152] From the viewpoint of preventing the formation of ferrite and inhibiting the precipitation and growth of carbides, the stop temperature of quenching is 200° C. or less based on the surface temperature of the rolled material. In particular, from the viewpoint of inhibiting the growth of carbides, the stop temperature of quenching is preferably 100° C. or less based on the surface temperature of the rolled material.
[0153] Here, A c3 is the starting temperature of phase change during heating calculated as follows, A r3 The phase transformation start temperature during cooling for the following calculation is calculated using the chemical composition of the steel.
[0154] A c3 (℃)=902-255×C+19×Si-11×Mn-5×Cr+13×Mo-20×Ni+55×V
[0155] A r3 (℃)=868-396×C+24.6×Si-68.1×Mn-24.8×Cr
[0156] In the above formula, C, Si, Mn, Cr, Mo, Ni, and V are contents expressed in mass %.
[0157] Example
[0158] The following are examples of the present disclosure. However, the following examples are examples of the present disclosure, and the present disclosure is not limited to the following examples. Example 1 is an example of direct quenching, and Example 2 is an example of reheating quenching.
[0159] <Example 1>
[0160] The thickness of the steel billet manufactured by smelting and continuous casting of steel using a converter is 245 mm. Samples were collected from the steel billet, and the chemical composition was analyzed using fluorescent X-ray analysis, combustion-infrared absorption, inert gas melting, inductively coupled plasma mass spectrometry (ICP mass spectrometry), etc. The results are shown in Table 1. In Table 1, a blank column means a value below the analysis lower limit. In addition, although not recorded in Table 1, the content of O as an impurity is 20ppm to 60ppm. In Tables 1 to 3, underlines refer to values or conditions outside the scope of the present disclosure.
[0161]
[0162] The steel slab is hot rolled and the rolled material is directly quenched to produce a steel plate (wear-resistant steel). The heating temperature for hot rolling is A c3 Above the phase transition point, the end temperature is A r3 In the hot rolling process, the rolled material is rolled at a temperature of 1000° C. or higher with a reduction ratio of 50% or higher.
[0163] Table 2 shows the steel No. of the steel slab used in the hot rolling, the starting temperature of quenching, the cooling rate, the stopping temperature, and the thickness of the steel plate.
[0164] (Metallic structure observation)
[0165] The metal structure of the steel plates of various thicknesses obtained was observed at the 1 / 2t portion when the thickness of the wear-resistant steel was less than 16 mm, and at the 1 / 4t portion when the thickness of the wear-resistant steel was more than 16 mm. The observation surface was the L (length) direction cross section of the sample, and wet grinding and etching with nitric acid were performed. The metal structure was observed at a magnification of 400 times, and the presence or absence of ferrite, pearlite, upper bainite and retained austenite was determined by observation of 5 fields of view. When structures other than lower bainite and martensite were observed, they were shown in Table 2 with the following symbols, and "-" was recorded when the following structures were not observed.
[0166] α: Ferrite
[0167] P: Pearlite
[0168] uB: Upper Bainite
[0169] γ: Retained austenite
[0170] (Measurement of the area ratio and average equivalent circle diameter of carbides)
[0171] The sample used in the observation of the metal structure was subjected to electrolytic grinding, and the area ratio and equivalent circle diameter of the carbide were measured by SEM. The area and number of carbides were measured by image analysis of a photograph taken at 30,000 times, and the area ratio and average equivalent circle diameter of the carbide were calculated. The area ratio and average equivalent circle diameter of the carbide are shown in Table 2.
[0172] It should be noted that carbides include Cr carbides and Fe2C in addition to cementite (Fe3C). Cr carbides are carbides that precipitate when kept at high temperature for a long time, but in the manufacturing process disclosed in the present invention, cooling is performed before the precipitation of Cr carbides. It is believed that if Cr carbides are precipitated, the solid solution Cr decreases, the hardenability decreases, and the solid solution C amount decreases, so the hardness as wear-resistant steel will not appear.
[0173] It is considered that Fe2C precipitates during low-temperature tempering (100 to 200°C), but the size is so minute that it can be observed by TEM (transmission electron microscope) and cannot be observed by SEM.
[0174] Based on these findings, it can be seen that the carbides observed in the examples are cementite.
[0175] (Measurement of effective crystal size)
[0176] Furthermore, the average of the top 10 grain sizes surrounded by high-angle grain boundaries of 15° or more was measured by EBSD. The measurement using EBSD was performed at a spacing of 0.4 μm in a field of view of 400 μm×400 μm. The average of the top 10 grain sizes surrounded by high-angle grain boundaries of 15° or more was obtained by OIM-Analysis manufactured by TSL. The average of the top 10 grain sizes surrounded by high-angle grain boundaries of 15° or more is shown in Table 2 as the effective crystal grain size.
[0177] (Vickers hardness test)
[0178] In the L (length) direction section of the sample, the Vickers hardness of the wear-resistant steel is measured at a position 0.7 mm from the surface of the wear-resistant steel in the thickness direction and at the 1 / 2t portion. The Vickers hardness test is carried out in accordance with JIS Z 2244:2009 with a load of 10 kgf. The Vickers hardness is the average value of any three points measured. If the surface hardness is 360 HV10 or more and 634 × [C] 1 / 2 +140HV10 or more, the wear resistance is good, and if the hardness of the 1 / 2t part is 360HV10 or more and 634×[C] 1 / 2 When the HV10 is +140 or more, the deterioration of the wear resistance is also well suppressed.
[0179] (Charpy test)
[0180] The Charpy test was performed using a full-size test piece with a V-notch in accordance with JIS Z 2242: 2018. The average value of the Charpy absorbed energy was the arithmetic average of the measured values of three test pieces. The length direction of the Charpy test piece was the rolling direction of the steel plate.
[0181] When the thickness of the wear-resistant steel is less than 12 mm, a small-sized test piece of 5 mm is used. Regarding the sampling position of the Charpy test piece, the wear-resistant steel with a plate thickness of 16 mm or more is the 1 / 4t part, and the wear-resistant steel with a plate thickness of less than 16 mm is the 1 / 2t part. Vickers hardness (surface hardness and 1 / 2t hardness) and Charpy absorbed energy (KV2) are shown in Table 2. If the Charpy absorbed energy is 27 J or more, the low-temperature toughness is good.
[0182] (Corrosion resistance test)
[0183] The corrosion resistance test was conducted based on the test methods of JASO M609 and JASO M610, using an artificial seawater solution diluted 1 / 100. One cycle consisted of 2 hours of salt spray, 4 hours of drying, and 2 hours of wetting. After 504 cycles of corrosion treatment, the rust was removed by pickling, and the corrosion rate was compared by the weight change before and after corrosion. Steels with a corrosion rate of less than 80% of that of ordinary steel SM490 were evaluated as A, and steels with a corrosion rate of more than 80% of that of ordinary steel SM490 were evaluated as B.
[0184]
[0185] <Example 2>
[0186] Steel slabs having the composition shown in Table 1 were hot rolled, and after air cooling, the rolled material was reheated and quenched to produce steel sheets. The heating temperature for hot rolling was A c3 Above the phase transition point, the end temperature is A r3 In the hot rolling process, the rolled material is rolled at a temperature of 1000°C or higher with a reduction ratio of 50% or higher. The heating temperature for reheating quenching is A c3 above the phase transition point.
[0187] Table 3 shows the steel No. of the steel slab used in the hot rolling, the starting temperature of quenching, the cooling rate, the stopping temperature, and the thickness of the steel plate.
[0188] The metal structure of each obtained thick steel plate was observed, the area ratio of carbides and the average equivalent circle diameter were measured, the effective crystal grain size was measured, the Vickers hardness and Charpy absorbed energy were measured, and the corrosion resistance test was performed in the same manner as in Example 1. The results are shown in Table 3.
[0189]
[0190] As shown in Tables 2 and 3, the steel sheets satisfying the requirements of the present disclosure do not contain Ni and Mo, or the contents thereof are suppressed to 0.50% or less, and are excellent in wear resistance, corrosion resistance, and low-temperature toughness.
[0191] In Production No. 101, since the C content was high, carbides were coarsened and the targeted low-temperature toughness was not obtained.
[0192] In Production No. 102, since the Cr content was low, carbides were coarsened and the targeted low-temperature toughness was not obtained.
[0193] In Production No. 103, since the C content was low, the surface hardness was insufficient and the targeted wear resistance was not obtained.
[0194] In Production No. 104, since the Mn content was high, a large amount of MnS, which became a starting point of brittle fracture, precipitated, and the targeted low-temperature toughness was not obtained.
[0195] In Production No. 105, since the quenching start temperature was low, ferrite was generated, and the targeted wear resistance and low-temperature toughness were not obtained.
[0196] In Production No. 106, since the cooling rate was slow, ferrite was generated and carbides were coarsened, and the targeted wear resistance and low-temperature toughness were not obtained.
[0197] In Production No. 107, since the quenching stop temperature was high, carbides coarsened and the targeted low-temperature toughness was not obtained.
[0198] In Production No. 108, since the C content was high, carbides were coarsened and the targeted low-temperature toughness was not obtained.
[0199] In Production No. 109, since the Cr content was low, carbides were coarsened and the targeted low-temperature toughness was not obtained.
[0200] In Production No. 110, since the C content was low, the surface hardness was insufficient and the target wear resistance was not obtained, and the low-temperature toughness was also insufficient.
[0201] In Production No. 111, since the Mn content was high, the targeted low-temperature toughness was not obtained.
[0202] In Production No. 112, since the quenching stop temperature was high, the targeted low-temperature toughness was not obtained.
[0203] In Production No. 113, since the quenching stop temperature was low, ferrite was generated and the surface hardness was insufficient, the targeted wear resistance was not obtained, and the low-temperature toughness was also insufficient.
[0204] In Production No. 114, since the cooling rate was slow, ferrite was generated and carbides were coarsened, and the targeted wear resistance and low-temperature toughness were not obtained.
[0205] In Production No. 115, since the quenching stop temperature was high, carbides coarsened and the targeted low-temperature toughness was not obtained.
[0206] The entire disclosure of Japanese Patent Application No. 2020-127724 filed on July 28, 2020 is incorporated herein by reference. All documents, patent applications, and technical standards described in this specification are incorporated herein by reference to the same extent as if each document, patent application, and technical standard were specifically and separately described.
Claims
1. A wear-resistant steel, the chemical composition of which is composed of the following elements in mass %: C:0.08%~0.20%、 Si: 0.01% to 0.50%, Mn: 0.10% to 2.00%, P: 0.015% or less, S: 0.0300% or less, Cr:2.10%~8.00%、 N: 0.0080% or less, Cu: 0% to 0.50%, Ni: 0% to 0.50%, Mo: 0% to 0.50%, V:0%~0.500%、 W:0%~0.50%、 B:0%~0.0050%、 Al:0%~0.300%、 Ti: 0% to 0.100%, Nb: 0% to 0.100%, Ca: 0% to 0.0100%, Mg: 0% to 0.0100%, REM: 0% to 0.0100%, and The rest: Fe and impurities, In a cross section in the thickness direction, when the thickness is set to t, when t is less than 16 mm, at a position 1 / 2t from the surface, and when t is 16 mm or more, at a position 1 / 4t from the surface, the carbides contained in the metal structure are 0% to 0.5% in terms of area %, the average equivalent circle diameter of the carbides is 500nm or less, in a region of 400μm×400μm, the average grain size of the first 10 grains in order of the largest grain size among grains surrounded by grain boundaries with a large inclination angle of 15° or more is 40μm or less, and the Charpy absorption energy at -40°C is 27J or more, When the C content in mass % is set to [C], the surface hardness at a position 0.7 mm from the surface in the thickness direction is 360 HV10 or more and 634×[C] 1 / 2 +140HV10 and above.
2. The wear-resistant steel according to claim 1, wherein the central hardness of the central portion in the thickness direction is 360 HV10 or more and 634×[C] 1 / 2 +140HV10 and above.
3. The wear-resistant steel according to claim 1 or claim 2, which contains at least one selected from the following elements in terms of mass %: Cu: 0.01% to 0.50%, Ni: 0.01% to 0.50%, Mo: 0.01% to 0.50%, V:0.003%~0.500%、 W:0.01%~0.50%、 B:0.0003%~0.0050%、 Al:0.005%~0.300%、 Ti: 0.003% to 0.100%, Nb: 0.003% to 0.100%, Ca: 0.0003% to 0.0100%, Mg: 0% to 0.0100%, and REM: 0.0003% ~ 0.0100%. The wear-resistant steel according to claim 1 or claim 2, which is a steel plate. The wear-resistant steel according to claim 3 , which is a steel plate.
6. The wear-resistant steel according to claim 4, wherein the thickness of the steel plate is 8 mm to 50 mm.
7. The wear-resistant steel according to claim 5, wherein the thickness of the steel plate is 8 mm to 50 mm.
Citation Information
Patent Citations
Manufacture of thick tough steel
JP1984070721A
Production of thick walled ultra high tension steel
JP1984129724A
Production of member with high toughness and high temperature wear resistance and thick steel plate therefor
JP1998102185A
Production of wear resistant member with high toughness and thick steel plate
JP1998204575A
Implantable medical device with bulk metallic glass enclosure
JP2020127724A